A Novel Transgenic Mouse Model of Hyperfibrinogenemia - Gulledge, Alyssa A.; Rezaee, Farhad; Verheijen, Jan H.; Lord, Susan T. (Thrombosis and Haemostasis, 2001)
Hyperfibrinogenemia is a risk predictor in several diseases, including cardiovascular disease. Nevertheless, it remains unknown whether elevated fibrinogen has an etiologic role in or is a reflection of disease pathogenesis, or both. To examine this question, we generated a mouse model of hyperfibrinogenemia. We isolated the mouse fibrinogen locus, containing the three fibrinogen genes, in a single P1 clone. This ~ 100 kb clone was injected into C57Bl/6J zygotes. Three transgenic lines were identified, two with elevated fibrinogen, 1.4- and 1.7-fold relative to normal. We characterized the line with the higher level. Northern blots of total RNA showed transgene expression was liver specific, and the message levels were 2- to 3-fold enhanced. Fibrinogen in transgenic mice was normal in both immunologic and clotting assays. Our data indicate that over-expression of all three fibrinogen genes is necessary to achieve hyperfibrinogenemia. We saw no increase in mortality or morbidity, no gross abnormalities in the organs, and no histologic differences in lung, liver, spleen or kidney, in transgenic mice relative to normal littermates. We conclude that elevated fibrinogen did not cause disease in mice. We anticipate that breeding these mice to other mouse models of disease will demonstrate whether hyper-fibrinogenemia has a role in the initiation or progression of symptomatic disease.
Keywords: Hyperfibrinogenemia; mouse models; fibrinogen